Sustainability Measurement of Farming System in Isfahan Agricultural Sector (Smallholders-Rural Production Cooperatives- Farm Corporation) - Saedali Nekooei Naenii; Yosef Ghanbari; Hamid Barghi (جغرافیا و پایداری محیط)
1-Introduction Low productivity in the agricultural sector, inappropriate use of production factors to enhance product performance during the last decade as a result of adverse environmental degradation and the need for sustainable production and food security prove the importance of sustainability of the agricultural farming systems. The basic condition for the sustainable use of nature is the observation of natural resources capacity. Indeed, this capacity is also determined by analysis or stability measurement. Stability Analysis is the basis and criteria to determine environmental standards in order to show the utilization of resources and control screw. Analysis the degree of stability in a decisive and stable condition and the measurement of the distance between the original and the new situation are considered as peripheral phenomena. At the same time the analysis of resource capacity and economic sustainability are analyze and controled in relation to production needs. Stability measurement is a complex interaction between technology, the environment and society. Farming systems are the most important and fundamental issue in agriculture sector in any country. In Iran, the biggest obstacle to the agricultural development and the realization of its strategic goals and structural barriers are related to farming systems. The optimal use of soil and water resources and increase production and productivity per unit, improve the quality of agricultural products through the land consolidation,training, promotion and application of modern agricultural science and technology, promotion of mechanization, scientific management, proper use of existing facilities with an emphasis on restoring an preserving the environment and prevent the destruction or waste of resources changing the hardware systems and even removing barriers, expand the area under cultivation or solving this structural problem, the creation of a qualitative transformation in the structure of agriculture, especially in agricultural systems are related to farming system. 2- Material and Methods As a matter of fact, it was impossible to collect data of 17362, 635, and 85405 farmers belonged to agriculture cooperatives, farm corporation and smallholder farmers, respectively due to geographical scope of the research included the province of Isfahan, and the widespread distribution of the statistical population. Therefore, it was decided to take samples. The sample size was calculated using Cochran's formula. Moreover, the sample size for each company and smallholder farmers systems were calculated by proportional assignment. Using random sampling method, the beneficiaries’ sample was selected. This research has been conducted as a combined study (quantitative and qualitative), applied research, descriptive (non-experimental) and the cross-sectional surveys. The date needed for documentary and field research (questionnaires and interviews) were collected. In this study, Shannon entropy method was used to analyze the data collected. 3- Results and Discussion The development of agriculture is not only an underlying necessity in the society, but also an inevitable extremity. The results from various studies suggest that the improvement of the agricultural production shall not be achieved unless the farming system is revised and reformed in line with the principles of a sustainable agriculture as the pivot of agricultural developments. The results show that small farming system is unstable in 17 villages, while in 10 villages is semi stable and the remaining 2 villages are in stable condition. Besides, 12 rural production cooperatives have unstable condition, eight cooperatives in a semi stable and remaining consist of eight rural production cooperatives are in stable condition, farming stock corporation is in stable condition. Farming Corporation is more stable in economic and environmental dimensions than the other two farming systems. In social dimension as membership in the local community, participation in agricultural activities small farming system is more stable than the other two farming systems, in economic dimension is unstable and in environmental dimension is semis table. Rural production cooperatives are unstable in economic and environmental dimensions and semi stable in social dimension. Farming Corporation is semi stable in economic and social dimensions and unstable in environmental. Increased using of nitrogen fertilizers, phosphate and pesticides have caused instability in all three types of farming systems. The magnitude of the instability is less in farming corporation than other two farming system for reasons of using technical factors. 4- Conclusions The average total income by production in smallholder farmers system is considered as one of unsustainable indices in the region, so certificating a price proportional to the production costs will be beneficial to increase the agricultural income. Despite applying the relatively new science and technology in planting, growing, and harvesting operations, the same index is unsustainable in thefarm corporation system, mainly due to the impact of the amount of dividends paid to cooperative members for the ability of managers. So, it is emphasized that related governmental organization pay special attention to pick out the qualified candidates for the Board of Directors in order to committee the managers and specialists with high throughput in the field of agriculture. Due to unsustainability of farm corporation in terms of the social dimension, it is recommended to apply innovative methods and cooperative approach in the formation of t. Besides, it is important to participate in these corporations during their establishment which depends on the performance of the corporations’ managers. Considering the fact that all three types of farming systems are unsustainable in terms of environmental dimension (smallholder farmers is most unsustainable, followed by rural production cooperatives and Farm Corporation), it shows few applied research conducted in this sector leading to the improvement of agricultural products and application ofnative technology in accordance with cultivation environment. Efficient research and development centers are essential to solve the environmental unsustainability in various aspects of agricultural production, which should be on the agenda of the agricultural research and development centers.